Benefit-to-harm ratio and cost-effectiveness of government-recommended gastric cancer screening in China: A modeling study - Qin, Shuxia; Wang, Xuehong; Li, Sini; Tan, Chongqing; Zeng, Xiaohui; Wu, Meiyu; Peng, Ye; Wang, Liting; Wan, Xiaomin (Frontiers in Public Health, 2022)
Objective: Current guidelines recommend the gastric cancer risk score scale (GCRSS) for screening in gastric cancer high risk populations in China. This study aimed to estimate the clinical benefits, harms, cost, and cost-effectiveness of the GCRSS screening strategy from a Chinese health care system perspective. Materials and methods: Using a microsimulation model, we evaluated 7 screening scenarios of the GCRSS with varying starting ages. We simulated 100000 individuals from the age of 20 for each screening scenario. The main outcomes included gastric cancer incidence reduction, number of cause-specific deaths, costs, quality-adjusted life year (QALY), incremental cost-effectiveness ratio (ICER), and benefit-to-harm ratio. Deterministic and probabilistic sensitivity analyses were done to explore the robustness of model findings. Results: Screening with the GCRSS strategy at age 40 years (40-GCRSS) provided the greatest reduction of GC incidence by 70.6%, with 7374 gastric cancer deaths averted per 100000 individuals and the lowest benefit-to-harm ratio of 0.392. Compared with no screening or previous less costly strategy, at a willingness-to-pay threshold of $12552 per QALY, the 40-GCRSS strategy was cost-effective, with ICERs of $8069 and $11921 per QALY, respectively. Results were robust across univariate and probabilistic sensitivity analyses. The 40-GCRSS strategy showed 0.989 probability of being cost-effective at a $37655 per QALY willingness-to-pay threshold. Conclusions: The findings suggest that the GCRSS strategy is effective and cost-effective in reducing the gastric cancer disease burden in China from a Chinese health care system perspective. Screening from the age of 40 would be the optimal strategy.